(untitled) (Fiep Bulletin - online, 2013)
A bibliographical documental study to describe “Segundo Tempo” Program and branches of its own to serve “Mais Educação” Program. It is possible to observe that that partnership is valid and necessary. From the year 2009 on, both Ministry of Sports and Education commune their policies setting conditions to offer educational sports through PST pedagogical proposal for schools participating in “Mais Educação” Program. Both programs presented in this study are examples of public policies which care about spreading sports practice in a way to overcome a concept of only practice. PST pedagogical proposal has the strong feature to commune with “Mais Educação” Program and the basis in a full time educational proposal. However, the study defends a major participation of Physical Education teachers. Schools, from our point of view, are institutions of greater power to act on cultural and educational changes, therefore, we conclude that the insertion of extra activities such as sports in political pedagogical projects for Brazilian public schools may make difference in this challenge of extending educational possibilities for sports.